2019
DOI: 10.15666/aeer/1702_25012517
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly Community Structure and Diversity in Sangihe Islands, North Sulawesi, Indonesia

Abstract: Butterflies have an important role in the ecosystem of Sangihe Island, North Sulawesi, Indonesia. Currently, data on the diversity of butterflies on the island are still lacking and have not been published yet. Therefore, this study was aimed to analyze the structure of the butterfly community and its diversity in Sangihe Island, North Sulawesi, Indonesia. The research was conducted from March 2018 to May 2018 in Sangihe Island, North Sulawesi. Sampling was performed at three types of habitat: a farm, a forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This situation is not surprising as Nymphalidae is the largest fam- ily with perhaps 650 species or 34.21% of all known butterflies (Widjaja 2014). On the other hand, the lowest number of species was recorded from the inconspicuous family of Hesperidae and is also similar to other areas in Indonesia, such as Baluran National Park (6.35%), Sangihe Island (0.64%), Talaud Island (3.12%) and Landsfill Balai Gadang (4.54%) (Leo et al 2016;Koneri & Nangoy 2019;Muhelni & Anwar 2020). Technical issues may also contribute to the low number of certain families.…”
Section: Species Diversitysupporting
confidence: 58%
“…This situation is not surprising as Nymphalidae is the largest fam- ily with perhaps 650 species or 34.21% of all known butterflies (Widjaja 2014). On the other hand, the lowest number of species was recorded from the inconspicuous family of Hesperidae and is also similar to other areas in Indonesia, such as Baluran National Park (6.35%), Sangihe Island (0.64%), Talaud Island (3.12%) and Landsfill Balai Gadang (4.54%) (Leo et al 2016;Koneri & Nangoy 2019;Muhelni & Anwar 2020). Technical issues may also contribute to the low number of certain families.…”
Section: Species Diversitysupporting
confidence: 58%
“…Ten butterfly families are reported from Sumatra: Acraidae, Amathusiidae, Danaidae, Hesperiidae, Lycaenidae, Nymphalidae, Papilionidae, Pieridae, Riodinidae, and Satyridae (Dahelmi et al 2010). There is very little information regarding the families and species of butterflies from offshore islands (Koneri and Nangoy 2019). This shows the importance of conducting further research to identify butterfly species found on offshore islands and understand the role and ecology of these species in the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies were conducted to observe the butterflies on small and outer islands in Greater Sunda. A study at an offshore island of Talaud Island, North Sulawesi, collected 32 species (Koneri and Nangoy 2019), while 33 species were recorded at Marak Island, Padang City (Dahelmi et al 2010). At Tanjung Balai Karimun, Riau Islands Regency, 42 species were identified (Nofri et al 2012), and 20 were found at Siberut Island of West Sumatra (Luk et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The variety of flowering plants at forest edges is related to the diversity of pollinating insects, especially from the Hymenoptera (Apoidea) (Widhiono et al 2017), and plays a vital role as a food resource for wild pollinating bees (Widhiono et al 2017). According to Filgueiras et al (2016), Pe′er et al (2011), Widhiono (2015, Orlandin et al (2019), and Koneri et al (2020), the diversity and abundance of butterfly populations are related to the diversity and abundance of flowering plants. In addition, forest edges also influence the diversity of wild bees (Rands and Whitney 2011;Roberts et al 2017).…”
Section: Introductionmentioning
confidence: 99%